Factors Affecting the Use of Mobile Banking as a Tool for Transactions and Financial Recording - Wardhatul Islamyi, Fiya; Suryaningrum, Diah Hari (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
This investigation seeks to elucidate the determinants that affect individuals' attitudes and intentions concerning the utilization of mobile banking by employing the frameworks of the Technology Acceptance Model (TAM) also the Unified Theory of Acceptance and Use of Technology (UTAUT). The factors in question are perception of security, perception of ease of use, perception of usefulness, also social influence. This research constitutes a quantitative analysis that employs primary data sources. The study’s population are undergraduate accounting students at 3 Universitas Pembangunan Nasional Veteran. The sampling’s technique utilized is purposive sampling with a total of 141 student respondents. This study employs the PLS SEM analytical method, facilitated by SmartPLS software version 4.0. The outcomes of this investigation demonstrate that the perception of security, perception of usefulness, perception of ease of use, also social influence exert a positively and statisically significant impact to attitudes towards the adoption of mobile banking. Additionally, attitudes toward mobile banking usage affect the intention to use mobile banking services. The implications of these findings demonstrate the importance of understanding mobile banking user behavior, both to strengthen the theoretical foundation of technology adoption models and to provide practical value to the banking sector in designing more effective digital strategies.